AUTOMATED DRAINAGE CHARACTERIZATION OF DUDGANGA WATERSHED IN WESTERN HIMALAYAS - Kuchay, Nissar A.; Bhat, M. Sultan (European Scientific Journal, ESJ, 2013)
Morphometric analysis of a drainage basin demonstrates the dynamic equilibrium that has been achieved due to interaction between matter and energy. It helps to understand the prevailing geo-hydrological characteristics of a catchment. The traditional manual approach for large scale watersheds is time consuming. Using an elevation raster or DEM as input to GIS it is possible to automatically delineate a drainage system and quantify the characteristics of the system. In the present study automatic delineation and drainage characterization of Dudganga catchment has been carried out for detailed analysis of its linear and areal parameters using ASTER Digital Elevation Model (DEM) together with hydrologic analysis tools in ArcGIS Spatial Analyst. Further Strahler’s scheme was used for stream ordering. The results reveal that the total number of streams is 890 belonging to different stream orders with the highest order of 6. The mean bifurcation ratio (Rb) value of 3.89 indicates that the geological structures are less disturbing the drainage pattern. The basin had medium drainage density (D) 1.21/Km2 indicating the moderately permeable subsoil and moderate vegetation cover. The stream frequency (Fs) of 1.41 exhibits a positive correlation with the drainage density value of the area indicating an increase in stream population with respect to increase in drainage density.